Connecting consumption and production systems from the perspective of the product user: a foundational multilevel systems model of circularity realized at the economy-scale - Svensson-Hoglund, Sahra; Russell, Jennifer D.; Richter, Jessika Luth; Kambanou, Marianna Lena; Velenturf, Anne P. M.; Grousset, Rich; Milios, Leonidas; Goldmark, Sandra; Calisto Friant, Martin; Gallego-Schmid, Alejandro; Novich, Laura; Dewick, Paul (Frontiers in Sustainability, 2025)
The Circular Economy (CE) concept continues to garner significant attention from stakeholders. Yet, what a CE entails in its realized state remains insufficiently articulated, particularly for product users. This study introduces a multilevel systems model that conceptualizes an economy-wide, fully implemented CE from the perspective of the product user. The focus is on the foundational tenets of CE theory, namely the flows of materials, products, and components in the specific context of durable consumer products. The model's development follows a sequential method and is empirically tested and refined through a Delphi study involving 14 experts in CE and sufficiency. First, this model clarifies the composition, elements, and structure of the consumption system in a realized CE. Notably, elements often relegated to the background, such as contextual settings, are foregrounded to enable a more comprehensive analysis of factors involved in CE behaviors. The model provides a structured foundation for systematic exploration of potential implications for product users, which can be expanded in future research to include additional dimensions (e.g., social and ecological). Second, the multileveled nature of the model and mapping of the diverse flows and interactions shaping product users' reality in a realized CE allows for systematic integration of consumption (i.e., more concrete from the perspective of the product user) and production (i.e., more abstract) systems. As such, the model introduces an integrated product-system lens for bridging multi- and interdisciplinary areas of sustainable consumption and production. The paper concludes by outlining avenues for future research and potential applications of the model.